The Understanding Of The Touristic Value Of Portuguese Overseas Monuments: The Case Of Angola (1959-1974) - Mariz, Vera (Journal of Tourism, Sustainability and Well-being, 2016)
The present study aimed to evaluate the understanding of the touristic value of Portuguese overseas monuments during Estado Novo, having as case-study the then colony of Angola between 1959 and 1974, years marked by the creation of the Information and Tourism Centre and the fall of the regime. Thus, considering the reality of the metropolis, we aimed to identify and analyse the evolution of tourism in this territory, as well the understanding and use of historic monuments by a nationalist regime as points of touristic interest and legitimisers of the national colonialism. We argue that during two different but totally complementary moments devoted to the relation between tourism and historic monuments of Angola, there was a real understanding of their touristic value. Besides that we claim that the believers of the touristic value of those monuments were very often advocates of the preservation or restoration of their pristine characteristics, an idea that we can affiliate to the thought of António Ferro to whom the success of tourism was extremely dependent on preserving and emphasizing the picturesque and idiosyncratic characteristics of those tourist destinations. To achieve our goals we have identified and analysed some tourism-related periodicals, thematic studies and legislation.